An Evaluation of English Textbook for Grade-6: Application of Communicative Approach - Jahan, Kalsoom; Mukhtar, Sumaira; Yasmin, Farhana; Mushtaq, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The study is investigating the assimilation of Pakistani English textbooks with communicative approach in material designing. This study takes into consideration the strengths, weaknesses and suggestions for necessary changes for Pakistani English Textbooks. A checklist based on CLT principles was developed for textbook analysis, to answer the research questions. The checklist items were related to physical attributes, goals, content, supported material and sequence of language skills: listening, speaking, reading, writing and grammar. English Text book of grade-6 published by “Punjab Text Book Board” was considered as teaching material. This book has been prepared according to the national curriculum 2006 and the national textbook and learning materials Policy 2007. To enhance the understanding of the results each unit of the text book was explored by the parameter of checklist, qualitatively and quantitatively. The results of the study show that English textbook needs to be revised according to the latest patterns of communicative language teaching and learning. Authentic texts from real environment should be included to give a rich encounter with natural spoken language that could help students in producing and generating language in real life. Listening material should also be included, as listening is the basic input skill which helps students in strengthening other communicative language skills.